2005
DOI: 10.1021/pr050113n
|View full text |Cite
|
Sign up to set email alerts
|

Extended Range Proteomic Analysis (ERPA):  A New and Sensitive LC−MS Platform for High Sequence Coverage of Complex Proteins with Extensive Post-translational ModificationsComprehensive Analysis of Beta-Casein and Epidermal Growth Factor Receptor (EGFR)

Abstract: We have developed a new and sensitive LC-MS platform, Extended Range Proteomic Analysis (ERPA), which is able to achieve very high sequence coverage and comprehensive characterization of post-translational modifications in complex proteins. This new platform provides advantages of both the top-down and bottom-up proteomic approaches by combining (i) digestion of the protein with an enzyme, such as Lys-C, which cuts less frequently than trypsin, leading to on average a higher molecular weight peptide size, (ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
191
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(200 citation statements)
references
References 45 publications
7
191
0
2
Order By: Relevance
“…An alternative method is the digestion of glycoproteins by Lys-C to generate a small number of peptides than tryptic fragments and the resultant larger peptides is analyzed by high resolution Fourier transform ion cyclotron resolution mass spectrometer. 18 However, it is not easy to identify large peptides if low resolution ion trap mass spectrometer is used. Multiple enzyme digestion strategy has been applied to the analysis of other modifications.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative method is the digestion of glycoproteins by Lys-C to generate a small number of peptides than tryptic fragments and the resultant larger peptides is analyzed by high resolution Fourier transform ion cyclotron resolution mass spectrometer. 18 However, it is not easy to identify large peptides if low resolution ion trap mass spectrometer is used. Multiple enzyme digestion strategy has been applied to the analysis of other modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins eluted from the gel slices and aliquots of the albumin-Trf-IgG-absorbed urinary protein preparation were digested with trypsin and endoproteinase Lys-C (Lys-C) for 1 hour at 37 o C, and lyophilized. Digestions of proteins eluted from gel slices [24] and from aliquots of the albumin-Trf-IgG-absorbed urinary protein preparation [25] were performed as previously described. LC-MS/MS analysis of digested urinary protein and gel slice preparations of urinary proteins was performed by Transitions Therapeutics, Inc. (Toronto, Ontario, Canada) and the Keck Biotechnology Resource Laboratory at Yale University (New Haven, CT, USA), respectively.…”
Section: Lc-ms/ms Analysis Of Urinary Protein Preparationsmentioning
confidence: 99%
“…The concept of Middle Down mass spectrometry has been in place for a while now [14], but it has not been until recent work by the Karger research group that this methodology was recognized as having potential as a new type of high-throughput proteomics platform. Wu et al showed that this Middle Down MS strategy termed Extended Range Proteomic Analysis could be used not only to obtain better sequence coverage than Bottom Up MS [81], but also could be performed under the same chromatographic conditions, and at similar sensitivities as Bottom Up MS. This group has gone on to improve large peptide separations and Middle Down MS analysis for the characterization of low levels of peptides carrying diverse kinds of PTMs [82].…”
Section: Can High-throughput Top Down Proteomics Be Reached?mentioning
confidence: 99%